2019
DOI: 10.1126/sciadv.aaw9562
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine N -oxide–derived zwitterionic polymers: A new class of ultralow fouling bioinspired materials

Abstract: Materials that resist nonspecific protein adsorption are needed for many applications. However, few are able to achieve ultralow fouling in complex biological milieu. Zwitterionic polymers emerge as a class of highly effective ultralow fouling materials due to their superhydrophilicity, outperforming other hydrophilic materials such as poly(ethylene glycol). Unfortunately, there are only three major classes of zwitterionic materials based on poly(phosphorylcholine), poly(sulfobetaine), and poly(carboxybetaine)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
212
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 189 publications
(214 citation statements)
references
References 39 publications
2
212
0
Order By: Relevance
“…74 Jaing et al also reported trimethylamine N-oxidederived zwitterionic polymers as a new class of ultralow fouling bioinspired materials. 75 These zwitterionic polymers and novel zwitterionic polymers will greatly contribute to the improvement of many medical devices due to their hydrated property. It is necessary to investigate in detail and consider that zwitterioinic polymer side-chains, which consist of cations and anions, significantly contribute to biocompatible due to the binding strength between cation/anion and water at the bio-interface.…”
Section: Zwitterionic Polymers As Biocompatible Polymersmentioning
confidence: 99%
“…74 Jaing et al also reported trimethylamine N-oxidederived zwitterionic polymers as a new class of ultralow fouling bioinspired materials. 75 These zwitterionic polymers and novel zwitterionic polymers will greatly contribute to the improvement of many medical devices due to their hydrated property. It is necessary to investigate in detail and consider that zwitterioinic polymer side-chains, which consist of cations and anions, significantly contribute to biocompatible due to the binding strength between cation/anion and water at the bio-interface.…”
Section: Zwitterionic Polymers As Biocompatible Polymersmentioning
confidence: 99%
“…Cell, platelet, and microbe adhesion are also major types of biofouling known to trigger inflammation and the FBR, so we continued to examine the performance of β‐HS in resisting these challenges. The β‐HS SAM efficiently resisted adhesion of fibroblast cells and platelets (Figure g–i, m), and also effectively resisted adhesion of fungi ( Candida albicans ), Gram‐positive bacteria ( Staphylococcus aureus ), and Gram‐negative bacteria ( Pseudomonas aeruginosa ) for at least 7 days (Figure i–k, n–p).…”
Section: Resultsmentioning
confidence: 99%
“…Apparently, as the distance between the oppositely charged moieties decreases, the level of hydration (number of bound water molecules) increases and the non-fouling properties are enhanced. With this principle in mind, Li et al [60] recently reported the preparation and use of polymers derived from trimethylamine N-oxide (TMAO)-a naturally occurring zwitterion in saltwater fish-in which the charged groups are linked to each other without any spacer between them (Figure 12). A TMAO-based polymer (PTMAO) was prepared as a fourth generation of zwitterionic anti-fouling agents.…”
Section: Zwitterionsmentioning
confidence: 99%